'On water' organocatalyzed enantioselective synthesis of highly functionalized cyclohexanones with an all-carbon quaternary centre from allylidene malononitriles and enones. Issue 2 (15th February 2017) - Vamisetti, Ganga B.; Chowdhury, Raghunath; Kumar, Mukesh; Ghosh, Sunil K.
Graphical abstract: Abstract: An organocatalyzed endo [4+2] cycloaddition between enones as pro-diene and allylidene malononitrile as dienophile leading to cyclohexanones with two 1, 3-related stereogenic centres and an all-carbon quaternary centre has been developed. The reactions were performed under 'green reaction' conditions using water as the reaction medium and ambient conditions. When allylidene cyanoacetate was used as the dienophile, cyclohexanones with three contiguous stereogenic centres, one of which is an all-carbon quaternary centre, were formed. The products were obtained in high yield and with acceptable diastereo- and enantioselectivity. Abstract : (2 S, 6 S )-2-Phenyl-4-oxo-6-styrylcyclohexane-1, 1-dicarbonitrile: C22 H18 N2 O [ α ]D 25  = −68.6 ( c 1.70 CHCl3 ) 73% ee Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-4-Oxo-2-(4-chlorophenyl)-6-styrylcyclohexane-1, 1-dicarbonitrile: C22 H17 ClN2 O [ α ]D 25  = −109.1 ( c 0.62 CHCl3 ) 96% ee Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-2-(4-Bromophenyl)-4-oxo-6-styrylcyclohexane-1, 1-dicarbonitrile: C22 H17 BrN2 O [ α ]D 25  = −151.4 ( c 0.46 CHCl3 ) ee >99.9% Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-2-(4-Fluorophenyl)-4-oxo-6-styrylcyclohexane-1, 1-dicarbonitrile: C22 H17 FN2 O [ α ]D 25  = −59.3 ( c 1.00 CHCl3 ) ee 72% Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-2-(4-Methoxyphenyl)-4-oxo-6-styrylcyclohexane-1, 1-dicarbonitrile: C23 H20 N2 O2 [ α ]D 25  = −60.5 ( c 1.49 CHCl3 ) ee 71% Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-2-(3-Chlorophenyl)-4-oxo-6-styrylcyclohexane-1, 1-dicarbonitrile: C22 H17 ClN2 O [ α ]D 25  = −71.2 ( c 0.81 CHCl3 ) ee 67% Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-2-(3-Bromophenyl)-4-oxo-6-styrylcyclohexane-1, 1-dicarbonitrile: C22 H17 BrN2 O [ α ]D 25  = −35.2 ( c 0.68 CHCl3 ) ee 65% Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-2-(4-Chlorostyryl)-4-oxo-6-phenylcyclohexane-1, 1-dicarbonitrile: C22 H17 ClN2 O [ α ]D 25  = −51.0 ( c 1.33 CHCl3 ) ee 70% Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-2-(4-Bromostyryl)-4-oxo-6-phenylcyclohexane-1, 1-dicarbonitrile: C22 H17 BrN2 O [ α ]D 25  = −42.8 ( c 1.25 CHCl3 ) ee 70% Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-2-(4-Fluorostyryl)-4-oxo-6-phenylcyclohexane-1, 1-dicarbonitrile: C22 H17 FN2 O [ α ]D 25  = −36.5 ( c 1.66 CHCl3 ) ee 71% Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-2-(4-Methoxystyryl)-4-oxo-6-phenylcyclohexane-1, 1-dicarbonitrile: C23 H20 N2 O2 [ α ]D 25  = −77.1 ( c 1.19 CHCl3 ) ee 66% Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-2-(4-Nitrostyryl)-4-oxo-6-phenylcyclohexane-1, 1-dicarbonitrile: C22 H17 N3 O3 [ α ]D 25  = −62.0 ( c 1.81 CHCl3 ) ee 82% Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (2 S, 6 S )-2-(4-Bromostyryl)-4-oxo-6-(4-bromophenyl)cyclohexane-1, 1-dicarbonitrile: C22 H16 Br2 N2 O [ α ]D 25  = −97.2 ( c 0.50 CHCl3 ) ee 75% Source of chirality: Asymmetric induction Absolute stereochemistry: (2 S, 6 S ) Abstract : (1 S, 2 S, 6 S )-Ethyl-1-cyano-4-oxo-2-phenyl-6-styrycyclohexane carboxylate: C24 H23 NO3 [ α ]D 25  = −75.9 ( c 1.41 CHCl3 ), ee 90% Source of chirality: Asymmetric induction Absolute stereochemistry: (1 S, 2 S, 6 S ) Abstract : (1 S, 2 S, 6 S )-Ethyl-2-(4-bromophenyl)-1-cyano-4-oxo-6-styrylcyclohexanecarboxylate: C24 H22 BrNO3 [ α ]D 25  = −59.0 ( c 3.26 CHCl3 ) ee 82% Source of chirality: Asymmetric induction Absolute stereochemistry: (1 S, 2 S, 6 S ) Abstract : (1 S, 2 S, 6 S )-Methyl-1-cyano-4-oxo-2-phenyl-6-styrycyclohexane carboxylate: C23 H21 NO3 [ α ]D 25  = −66.9 ( c 2.28 CHCl3 ) ee 91% Source of chirality: Asymmetric induction Absolute stereochemistry: (1 S, 2 S, 6 S )